Методологічні підходи до формування професійної компетентності майбутніх маркетологів - Адамів, Світлана Євгенівна (Педагогіка і психологія професійної освіти : наук.-метод. журн. – Львів, 2016. – № 3., 2016)
In the modern conditions of Ukraine's economy one of the most important factors of improving the enterprise competitiveness is the development of methodological approaches to training future marketers and implementation of marketing activities in general. Changing the paradigm of society economic development requires modernization of contemporary higher economic education, which is the basis for determining the reserves of increasing the quality of training in marketing by the means of the development and implementation of basic scientific approaches to the formation of students' professional competence. The study analyzes the main scientific approaches that take into account the specific points of marketing activities, which allows us to work at the problem of formation of future marketers’ professional competence on a new level. The need for a comprehensive theoretical analysis of the formation of professional competence of students-marketers led marketers to using within the study such scientific approaches as competency, creative, communicative, informative and integrative. In the process of professional training of the future marketers the implementation of the outlined approaches is the basis of the educational transition to a higher level. It ensures the effectiveness of formation of students' professional competence, defines the guidelines for subjects of educational activities aimed at integrating their capabilities (development of marketing thinking, mastery of methodology and design and analytical skills to develop a strategy and to determine the effectiveness and optimization of business; expression of communicative skills; mobility skills and foreign language business communication; gain experience of marketing activities). Complementary implementation of outlined scientific approaches in the Higher Economic School facilitates the formation of future marketers’ professional competence.
Keywords: professional competence, future marketing, competence, creative, communicative, informative, integrative, scientific approach.